Kinetic Investigation of AISI 304 Stainless Steel Boronized in Indirect Heated Fluidized Bed Furnace - topuz, polat (Journal of Mining and Metallurgy, Section B: Metallurgy, 2015)
In this study, kinetic examinations on boronized AISI 304 Stainless Steel samples were described. Samples were boronized in indirect heated fluidized bed furnace consists of Ekabor 1™ boronizing agent at 1123, 1223 and 1323 K for 1,2 and 4 hours. Morphologically and typically examinations of borides formed on the surface of steel samples were studied by optical microscope, scanning electron microscope (SEM) and X-Ray diffraction (XRD).Boride layer thickness formed on the steel X5CrNi 18-10 ranges from 12 to 176µm. The hardness of the boride layer formed on the steel X5CrNi 18-10 varied between 1709 and 2119 Hv0,1. Layer growth kinetics were analyzed by measuring the extent of penetration of FeB and Fe2B sublayers as a function of boronizing time and temperature. The kinetics of the reaction has been determined with K=Ko exp (-Q/RT) equation. Activation energy (Q) of boronized steel X5CrNi 18-10 was determined as 244 kj/mol.